Pharmacokinetics, Safety, and Tolerability of Fevipiprant (QAW039), a Novel CRTh2 Receptor Antagonist: Results From 2 Randomized, Phase 1, Placebo‐Controlled Studies in Healthy Volunteers. Issue 4 (28th March 2016) - Erpenbeck, Veit J.; Vets, Eva; Gheyle, Lien; Osuntokun, Wande; Larbig, Michael; Neelakantham, Srikanth; Sandham, David; Dubois, Gerald; Elbast, Walid; Goldsmith, Paul; Weiss, Markus
Abstract: We evaluated the pharmacokinetics (PK), safety, and tolerability of a novel oral CRTh2 antagonist, fevipiprant (QAW039), in healthy subjects. Peak concentrations of fevipiprant in plasma were observed 1‒3 hours postdosing. Concentrations declined in a multiexponential manner, followed by an apparent terminal phase (t1/2, ∼20 hours). Steady state was achieved in 4 days with <2‐fold accumulation. Elimination was partly by renal excretion (≤30% of the dose) and glucuronidation. Food had minimal impact on the PK of fevipiprant, and it was well tolerated at single and multiple oral doses up to 500 mg/day. No dose‐dependent adverse events were observed, and all the events were mild or moderate in severity. Systemic concentrations were sufficiently high to achieve relevant target occupancy, considering in vitro pharmacology data. In summary, the data support further development as a once‐daily oral therapy for allergic diseases.